Построение оценок решений в модели противоопухолевого иммунитета с импульсными возмущениями - Марценюк, В.П.; Андрущак, И.Е.; Гвоздецкая, И.С. (Кибернетика и системный анализ, 2012)
Запропоновано модель протипухлинного імунітету з імпульсними збуреннями відносно популяції проліферуючих клітин. Отримано асимптотичні оцінки розв’язків рівнянь. Оцінки будуються на основі імпульсних диференціальних нерівностей для функцій типу Ляпунова The authors propose a model of antitumor immunity with impulsive perturbations with respect to the population of proliferating cells. The asymptotic estimates of are obtained for solutions of the equations. The estimates are based on impulsive differential inequalities for Lyapunov-type functions